(untitled) (CIPEEX, 2025)
Syphilis is a systemic bacterial infection, caused by Treponema pallidum, transmitted mainly through sexual contact, but also from mother to child during gestation. In Brazil, in recent years, a significant increase in syphilis cases has been observed, especially among young women and pregnant women. A study conducted in Anápolis, Goiás, pointed to an increase in syphilis notifications between 2012 and 2018, with a sharp growth in cases among pregnant women. The study methodology included data collection from the Notifiable Diseases Information System (SINAN), covering sociodemographic and clinical aspects of cases reported between 2018 and 2022. The results showed 2,401 syphilis notifications in Anápolis, with a higher prevalence among men and people aged 20 to 39. Formal education appears to influence awareness about the infection, and the majority of cases occurred among individuals who self-declared as mixed-race (Pardo). The analysis also revealed difficulties in data collection, with many cases unreported. The conclusion emphasizes the urgent need for awareness campaigns and improvements in case reporting, highlighting that prevention efforts are essential to control the spread of syphilis in the region. Data collection and analysis are fundamental for directing public health strategies and reducing the incidence of the disease in Brazil.